2018
DOI: 10.1186/s10194-018-0902-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between migraine and physical exercise

Abstract: BackgroundThere is an unmet need of pharmacological and non-pharmacological treatment options for migraine patients. Exercise can be used in the treatment of several pain conditions, including. However, what exact role exercise plays in migraine prevention is unclear. Here, we review the associations between physical exercise and migraine from an epidemiological, therapeutical and pathophysiological perspective.MethodsThe review was based on a primary literature search on the PubMed using the search terms “mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
116
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(153 citation statements)
references
References 109 publications
9
116
0
9
Order By: Relevance
“…Despite the pharmacological interventions available to prescribing treatment providers, 15 there exists a need for adjunctive non‐pharmacological treatment for migraine 16 . Points of inquiry have included self‐management approaches, 17 and it has been suggested that regular exercise may exert prophylactic effects 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the pharmacological interventions available to prescribing treatment providers, 15 there exists a need for adjunctive non‐pharmacological treatment for migraine 16 . Points of inquiry have included self‐management approaches, 17 and it has been suggested that regular exercise may exert prophylactic effects 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the pharmacological interventions available to prescribing treatment providers, 15 there exists a need for adjunctive non‐pharmacological treatment for migraine 16 . Points of inquiry have included self‐management approaches, 17 and it has been suggested that regular exercise may exert prophylactic effects 16 . There is general interest in the headache field in developing a better understanding of which types of modifiable positive health behaviors, such as physical activity and fruit and vegetable consumption, can be drawn upon in reducing the individual migraine burden.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the role of social determinants of migraine in aging samples is needed in order to better characterize risk and disease course among those with co-morbid medical conditions and multiple medications, which may affect treatment. [21][22][23] There is support for exercise regimes as a treatment option for migraine, 24 however, our understanding of the mechanisms in which aerobic exercise may exert positive effects, and corresponding therapeutic considerations (eg, dose) for such activities is not yet understood, hindering the use of exercise as a treatment option. 18 Non-pharmacological treatment of migraine is a rapidly expanding field, with special attention being given to a variety of lifestyle factors which may ameliorate risk, including exercise.…”
mentioning
confidence: 99%
“…17 Among older migraineurs, medication options are reduced and non-pharmacological options may be of particular interest to prescribing health care practitioners and patients alike. 25 Gaining an understanding of the potential therapeutic benefit of physical activity in migraineurs is warranted given its affordability and ability to be administered on a large scale, 24 making it a potentially equitable treatment option. 19 Traditional recommendations for the treatment of chronic pain have excluded physical activity, however, a recent overview of Cochrane Reviews 20 demonstrated that while the quality of the evidence for physical activity/exercise as an intervention is low, there were positive effects and further study with increased methodological rigour is needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation